On education - Brighouse, Harry (London ; New York Routledge, 2006)
Addressing some of the most critical issues in education today, this text argues that schooling should be guided by a fundamental principle that is often overlooked by politicians and policy makers - the moral interests of the children being taught.
Keywords: Citizenship -- Study and teaching. Education -- Aims and objectives. Éducation civique